Pengaruh Model Pembelajaran Kooperatif Tipe STAD disertai Media Kartu Soal Berbentuk Puzzle terhadap Hasil Belajar Fisika Siswa SMP - Alma Alma; Muhammad Jarnawi (Jurnal Kreatif Online, 2021)
The study aimed to determine whether there was an effect of the STAD type cooperative learning model using the puzzle question card media on the physics learning outcomes of junior high school students. This type of research was the quasi-experimental with the equivalent pretest posttest group design. The sampling technique used in this research was purposive sampling. The research sample was 25 students of class VIII B as the experimental group and 25 students of class VIII E as the control group. The instrument for learning physics was in the form of multiple-choice test questions. The results test showed the average value of the experimental group was 20.02 with a standard deviation of 2.73 and in the control class, the average value was 16.82 with a standard deviation of 2.81. Hypothesis test t-test (two-tailed) obtained tcount = 4.08 and ttable = 2.02 at the level of significance = 0.05. It shows that tcount is outside the H0 acceptance region. So, it can be concluded that there is an effect of the STAD type cooperative learning model using the puzzle question card media on the physics learning outcomes of junior high school students.